Integrasi Social-Emotional Learning dalam Pembelajaran Pendidikan Agama Islam: Dampaknya terhadap Empati, Regulasi Diri, dan Pembentukan Karakter Siswa Sekolah Dasar - Ahmad Saiful Alim; Iwan Kuswandi; Zainuddin (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to analyze the effect of integrating Social-Emotional Learning (SEL) into Islamic Religious Education (PAI) learning on elementary school students’ empathy, self-regulation, and character development. The study employed a quantitative approach with a quasi-experimental design using a nonequivalent control group pretest–posttest model. The research subjects consisted of 60 fourth-grade students at SDIT Al Hidayah, who were divided into an experimental group and a control group. The experimental group received PAI instruction integrated with SEL, while the control group followed regular PAI instruction. Data were collected using an empathy scale, a self-regulation scale, and a character observation rubric. Data analysis was conducted using analysis of covariance (ANCOVA) with pretest scores as covariates. The results indicated that the integration of SEL into PAI learning had a significant effect on improving students’ empathy, self-regulation, and character development (p < 0.05). Among the measured variables, self-regulation showed the largest effect size compared to the others. These findings demonstrate that PAI learning integrated with SEL is more effective in developing students’ social-emotional competencies and character than conventional PAI instruction. This study contributes to the development of a contextual PAI learning model that is relevant to the demands of 21st-century education.